Structural, chemical, and magnetic investigation of a graphene/cobalt/platinum multilayer system on silicon carbide - Weinert, Philipp (Technische Universität Dortmund, 2024)
Spintronics offers huge potential for data storage and processing and, thus, for overcoming the challenges arising from the ever-increasing demands in the field of electronics. To fully utilize this potential in real-world applications, appropriate materials are required. Graphene-ferromagnetic interfaces show great promise in this context. Combining graphene with a ferromagnet, such as cobalt, results in a system with many advantageous effects, such as Dzyaloshinskii−Moriya interaction (DMI). These effects allow for the formation of useful spin structures with high stability. Furthermore, such structures can also be induced in cobalt by combining it with a heavy non-magnetic metal such as platinum. In this study, the magnetic interlayer coupling and domain structure of ultra-thin ferromagnetic cobalt (Co) layers embedded between a graphene (G) layer and a platinum (Pt) layer on a silicon carbide (SiC) substrate (G/Co/Pt on SiC) were investigated. The $(6\sqrt{3} \times 6\sqrt{3}) \text{R}\ang{30}$-reconstruction was prepared on SiC and served as a precursor for graphene. It was prepared using two techniques, namely confinement controlled sublimation (CCS) and polymer assisted sublimation growth (PASG). Consequently, the sample properties varied slightly. Following this, the metal layers were prepared by intercalation. Experimentally, a combination of x-ray photoemission electron microscopy (X-PEEM) with x-ray magnetic circular dichroism (XMCD) was carried out at the Co L-edge to study the system's magnetic structure. Furthermore, structural and chemical properties of the system were investigated using low-energy electron diffraction (LEED) and x-ray photoelectron spectroscopy (XPS). In-situ-LEED patterns revealed the crystalline structure of each layer within the system. Moreover, XPS confirmed the presence of quasi-freestanding graphene and the absence of cobalt silicide. These characteristics of a clean and homogeneous Co-layer provide an excellent foundation for magnetic features to form. The magnetic structure of all samples exhibited numerous spin vortices and anti-vortices. In spintronics, these can be used as data carriers. The general magnetic structure of the material is heavily influenced by the preparation method. Different aspects were identified, which enhance or impede the formation of vortices.

Die Spintronik bietet enormes Potenzial im Bereich der Datenspeicherung und -verarbeitung und zur Überwindung der immer weiter steigenden Anforderungen im Bereich der Elektronik. Um dieses Potenzial zu nutzen, werden geeignete Materialien benötigt. Diesbezüglich sind Graphen-Ferromagnet-Grenzschichten besonders vielversprechend. Wird Graphen mit einem Ferromagneten, wie Kobalt, kombiniert, ergibt sich ein System mit vielen vorteilhaften Eigenschaften, wie Dzyaloshinskii−Moriya Wechselwirkung (DMI). Diese ermöglichen die Bildung von stabilen, nützlichen Spin-Strukturen. Solche Strukturen können ebenfalls in Kobalt hervorgerufen werden, wenn es mit einem schweren, nicht magnetischen Metall, wie Platin, in Verbindung steht. In dieser Arbeit wurde die magnetische Grenzschicht-Kopplung und Domänenstruktur von ultradünnen ferromagnetischen Kobaltschichten zwischen Graphen und Platinschichten auf einem Siliziumcarbidsubstrat (SiC) untersucht. Die $(6\sqrt{3} \times 6\sqrt{3}) \text{R}\ang{30}$-Rekonstruktion von SiC diente als Vorstufe für Graphen. Sie wurde mit zwei Methoden präpariert, der Raumbegrenzten-Sublimation (CCS) und der Polymere-unterstützen Sublimation (PASG). Diese führten zu leicht verschiedenen Probeneigenschaften. Anschließend wurden die Metallschichten mittels Interkalation präpariert. Die magnetische Struktur des Systems wurde mittels Synchrotronstrahlung angeregter Photoemissions-Elektronenmikroskopie (X-PEEM) an der Kobalt-L-Kante unter Nutzung des zirkularen magnetischen Röntgendichroismuses (XMCD) untersucht. Strukturelle Eigenschaften wurden mittels niederenergetischer Elektronenbeugung (LEED) und chemische mittels Röntgen-Photoelektronenspektroskopie (XPS) analysiert. in-situ-LEED-Messungen zeigten die kristalline Struktur jeder Schicht im System. Mittels XPS wurde quasi-freistehendes Graphen und die Abwesenheit von Kobaltsiliziden nachgewiesen. Die somit reine und homogene Kobaltschicht bildet eine hervorragende Grundlage für die Ausbildung von Spin-Strukturen. Die magnetische Struktur aller Proben zeigte eine Vielzahl von Spinwirbeln und -antiwirbeln. In der Spintronik können diese als Datenträger genutzt werden. Die generelle magnetische Struktur wurde stark von der verwendeten Präparationsmethode beeinflusst. Verschiedene Aspekte wurden entdeckt, die die Bildung von Spinwirbeln begünstigen oder erschweren.
About the formation of magnetic structures in 2D cobalt layers
Keywords: Epitaxial graphene; Metal intercalation; Magnetic imaging; Dzyaloshinskii-Moriya interaction; Graphene-ferromagnet interface; x-ray photoemission electron microscopy (X-PEEM); 530; Spintronik; Graphen; Ferromagnetikum; Grenzschicht; Photoemissionselektronenmikroskopie